Unilateral plyometric jump training shows significantly more effective than bilateral training in improving both time to stabilization and peak landing force in single-leg lend and hold test: A randomized multi-arm study conducted among young male basketball players - Zhao, Y. Sun, M.; Wang, X.; Xu, Q. (Journal of Sports Science & Medicine, 2024)
Enhancing peak landing forces and ensuring faster stabilization in the lower limbs during jumping activities can significantly improve performance and decrease the risk of injury among basketball players. This study aimed to compare the effects of unilateral (uPJT) and bilateral plyometric jump training (bPJT) programs on various performance measures, including countermovement jump (CMJ), squat jump (SJ), and single-leg land and hold (SLLH) test outcomes, assessed using force plates. A randomized multi-arm study design was employed, comprising two experimental groups (n = 25; uPJT and n = 25; bPJT) and one control group (n = 25), conducted with youth male regional-level basketball players (16.3 ± 0.6 years old). Participants underwent assessment twice, both before and after an 8-week intervention training period. The uPJT program exclusively involved plyometric drills (e.g., vertical jump exercises; horizontal jump exercises) focusing on single-leg exercises, whereas the bPJT program utilized drills involving both legs simultaneously. The outcomes analyzed included CMJ peak landing force, CMJ peak power, SJ peak force, SJ maximum negative displacement, SLLH time to stabilization, and SLLH peak landing force. The control group exhibited significantly greater SLLH time to stabilization compared to both the uPJT (p < 0.001) and bPJT (p < 0.030) groups. Additionally, time to stabilization was also significantly higher in bPJT than in uPJT (p = 0.042). Comparisons between groups in regards SLLH peak landing force after intervention revealed that the value was significantly smaller in uPJT than in bPJT (p = 0.043) and control (p < 0.001). In the remaining outcomes of CMJ and SJ, both uPJT and bPJT showed significant improvement compared to the control group (p > 0.05), although there was no significant difference between them. In conclusion, our study suggests that utilizing uPJT is equally effective as bPJT in enhancing performance in bilateral jump tests. However, it significantly outperforms bPJT in improving time to stabilization and peak landing forces during single-leg land and hold test. uPJT could be advantageous not for maximizing performance but also for potentially decreasing injury risk by enhancing control and balance during single-leg actions, which are common in basketball.